Regulation of proliferative response by SETD7 in breast cancer - Martins, Beatriz Corte Real (2019)
Breast cancer growth is dependent on stimulation by the ovarian hormone estrogen. Estrogen activates estrogen receptora (ERa) which is a ligandactivated transcription factor. Estrogen-bound ERa transactivates genes which stimulate proliferation and survival. Hormonal therapy is an effective strategy to treat hormone-related breast cancer. However, it is associated with endocrine resistance and recurrence. Activation of growth factors signaling pathways and alterations on ERα protein have been propossed as resistance mechanisms. ERa protein stability and activation of transcription is regulated by post transcriptional modifications such as methylation and by proteasome degradation. SETD7 is a methyltransferase which targets histones and others non-histone proteins important for cellular proliferation, including ERa. Methylation of ERa seems to contribute to ERa stability and activity; this would lead to an increase in cell survival. However, previous results from our lab indicate that SETD7 inhibits mammary epithelial cell proliferation. Therefore, in this project, we intent to study the co-regulation between ERa and SETD7 as well as the subsequent effects on proliferation in response to different mitogenic stimuli, with focus on estrogen. For this purpose, we used a SETD7 activity inhibitor known as R-PFI. In this study, we show that SETD7 levels decrease when cells are stimulated to proliferate. Inhibition of SETD7 activity by R-PFI leads to an increase in cell number. However, when cells were co-treated with R-PFI and estrogen the increase was not significant once cells suffer a cell cycle arrest. In the presence of R-PFI, we show an increase of ERa protein levels, identical to the levels obtained when ERa degradation is impaired by blocking the proteasome, suggesting that SETD7 may control ERa protein levels at this level. However, this increase of ERa levels did not translate into an increase of ERa activity. Thus, SETD7 can be dispensable for ERa activity. Our findings suggest an inhibitory role of SETD7 in breast cells growth in the absence of estradiol. But, on the other hand, our results do not support studies previously reported in relation to ERa regulation. Therefore, further studies are needed to establish SETD7 function in ERα- induced proliferation.